Chaste, Fair, and Bountiful: Marston, Fletcher, and the Countess of Huntingdon’s Patronage - Kolkovich, Elizabeth Zeman (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This essay uncovers the influences of Elizabeth Stanley Hastings, countess of Huntingdon (1588-1633), on household and commercial drama. John Marston’s Ashby entertainment (1607) and John Fletcher’s The Faithful Shepherdess (ca 1608) show how Huntingdon drew upon family tradition and conventional ideals of beauty to facilitate her rise as a patron. A focus on patronage reveals these plays’ shared emphasis on feminine authority within traditional roles. More broadly, this essay urges scholars to reconceive women patrons as co-makers of plays and value their important contributions to theatrical production.